طقوس الاحتفال بالمولد النبوي في زوايا الزيبان - نوارخرخاشي عبد المنعم (جامعة البليدة2- كلية العلوم الإنسانية والإجتماعية, 2025)
تندرج هذه الدراسة في حقل الانثروبولوجيا لموضوع طقوس الاحتفال بالمولد النبوي في زوايا الزيبان الزاوية القادرية والعثمانية والمختارية في بسكرة أنموذجا لمحاولة فهم الطقوس الاحتفالية واستمرارها في المجتمع الجزائري برغم التغير الاجتماعي؛ من خلال دراسة ميدانية لزوايا الزيبان التي لاتزال تحافظ على طقوسها الاحتفالية بمناسبة المولد؛ طقوس الاحتفال المتنوعة و الثرية في الزوايا الثلاث المختارة، هذه من طقوس الزيارة والضيافة والاطعام والدروس والانشاد والمديح والتحلية الاكرامية والتكريم، وكل الطقوس التي عايشها وشاركها الباحث وقد أدرجها في دراسته الميدانية، واداة الملاحضة بالمشاركة، وجمع البيانات الحقلية والصور من خلال الأداة الجديدة التي قام بإدخالها وتطوير عملها في حقل الانثروبولوجيا وهي أداة سالفي SELFIE TOOL ، وفق اخر تعديل للاداة لنجاعة وعلمية أكبر، وقد شغل واشتغل الباحث منهج جديد سماه منهج الوصف المجزأ Segmented Description Method؛ وفق خطواته وشروطه لما له من تيسير للبحوث الوصفية للظواهر الاجتماعية، كمحاولة لوضع الباحث الانثروبولوجي والاجتماعي في الزمن المعرفي الحقيقي، والدفع نحو استخدام ادوات جديدة ومناهج حديثة في عصرنا هذا، كما قمنا به لتطوير العلوم الإنسانية و الاجتماعية، ومواكبة مختلف العلوم بالاعتماد على التكنولوجيا المتقدمة الحديثة، وفق رؤية الانثروبولوجية للباحث، والكشف عن الطقوس وفق مقاربة إيرفينغ غوفمان في الطقوس التي وجدنها طقوس إيجابية تعمل على اندماج المجتمع وتقاربه واستمراره هذه الاحتفالية التي تنبع من ثقافة واصالة المجتمع الجزائري وموروثه الحضاري طقوس الاحتفال بالمولد النبوي التي تأبى الاندثار رغم كل بوادر الحداثة والتغيير. This study falls within the field of anthropology, The Rituals of Prophet AL NABI MOHAMED Celebration in the Ziban BISKRA Zawiyas, A Case Study of the ALQadiriya, ALOthmaniya, and ALMokhtariya. To explore in an attempt to understand the celebratory rituals and their continuity in Algerian society despite social change, through a field study of the Zawiyas of the Ziban that still preserve their celebratory rituals on the occasion of the Mawlid; the diverse and rich celebration rituals in the three selected Zawiyas, which include rituals of visiting, hospitality, feeding, lessons, singing, praise, sweets, and honoring, along with all the rituals experienced and shared by the researcher that were included in the field study. The method of participant observation was used, gathering field data and images through a tool that was introduced and developed in anthropology, the SELFIE TOOL, according to the latest modifications for greater efficiency and scientific rigor. The researcher employed a new methodology called the Segmented Description Method; according to its steps and conditions for facilitating descriptive research on social phenomena, as an attempt to place the anthropologist and social researcher within the true knowledge time, and to push toward the use of new tools and methodologies, as we did to develop human and social sciences, keeping pace with various sciences based on advanced modern technology, according to the researcher's anthropological vision, and revealing the rituals according to Erving Goffman's approach in the rituals that we found to be positive rituals promoting community integration, proximity, and continuity. This celebration emanates from the culture and authenticity of Algerian society and its civilizational heritage, the rituals celebrating the Prophet's birthday that refuse to fade away despite all signs of modernity and change.
الزاوية العثمانية والقادرية و المختارية في بسكرة أنموذجا
Keywords: مقاربات في الطقوس; الطقوس والشعائر والمولد; المولد النبوي